Assessment of Risk Factors among Renal FailurePatients in Baghdad Teaching Hospital - jawad, ahmed; okab, ammar (Iraqi National Journal of Nursing Specialties, 2017)
Objective(s): To identify the relationship between demographic characteristics of patients with renal failure and to find out the relationship between some risk factors like (family history, alcohol drinking, smoking and chronic disease) with renal failure patients. Methodology: Case control study design was carried out in order to achieve the objectives of the study by using the assessment technique in Baghdad teaching hospital from March 5 th, 2017 to October 10th , 2017, The sample was (cases & control) sample, present study include 200 cases, 100 was case study the patient who entered in Baghdad teaching hospital, while another 100 was control study. The data was collected by interview questionnaire including the purpose of study by the investigator and the data obtained through face to face. Data was analyzed that of case control study including (frequency, percent, odds ratio and confidence interval). Therefore, discriminating analysis was performed, discriminating analysis was performed, with the level of significant set at P ≤ 0.05. Results: Results presented that 30.5% of study was having acute renal failure, and highly statistical significant association between the items related to the Family history of renal failure and with groups (cases and control). Recommendations: The study recommended that increase awareness about the health risks of renal failure through educational programs and seminars and the provision of modern equipment and medicines that help diagnosis and treatment